Public-Private Partnerships in Urban Bus Systems : An Analytical Framework for Project Identification and Preparation - Hoyos Guerrero, Alejandro (Washington, DC: World Bank, 2021)
Many cities have sought to replicate the urban bus public-private partnership (PPP) structures that succeeded at the beginning of the millennium, such as those implemented in Brazil, Colombia, and Mexico. These cities improved their public transportation systems in the face of rapid urbanization, rising air pollution, and increasing road safety incidents through these PPP interventions. Examining these past international experiences, and others, Public-Private Partnerships in Urban Bus Systems: An Analytical Framework for Project Identification and Preparation first challenges the assumption that PPP structures are always the optimal approach for improving urban bus systems. The authors use relevant case studies to demonstrate that structuring such PPPs in cities in the developing world requires tailor-made interventions that respond to local contexts. The authors identify essential elements for PPP feasibility and invite readers to consider alternative solutions for achieving the desired objectives. This book presents an analytical framework that public transportation practitioners can use to support the process of identifying and preparing appropriate technical, financial, and legal structures to improve urban mobility if a PPP is the preferred solution. It follows a detailed, risk-based approach to thoroughly analyze the challenges that might be experienced by cities that pursue private participation in proposed urban bus interventions. Using specific examples, the authors thoroughly analyze the risks and the specific potential planning-stage challenges likely to be encountered and suggest strategies for practitioners to respond to the specific local contexts and the various alternative solutions. This study builds upon international experiences, predominantly in Latin America and in PPPs focused on streamlining fleet provision and operation. Finally, the book helps to identify and define bankable project structures that could respond well to local contexts and minimize risks.